The effect of dopamine agonists on adaptive and aberrant salience in Parkinson's disease - Nagy Helga; Levy-Gigi Einat; Somlai Zsuzsanna; Takáts Annamária; Bereczki Dániel; Kéri Szabolcs (2012)
Clinical evidence suggests that after initiation of dopaminergic medications some patients with Parkinson's disease (PD) develop psychotic symptoms, such as hallucinations and delusions. Here, we tested the hypothesis that the neurocognitive basis of this phenomenon can be defined as the formation of arbitrary and illusory associations between conditioned stimuli and reward signals, called aberrant salience. Young, never-medicated PD patients and matched controls were assessed on a speeded reaction time task in which the probe stimulus was preceded by conditioned stimuli that could signal monetary reward by color or shape. The patients and controls were re-evaluated after 12 weeks during which the patients received a dopamine agonist (pramipexole or ropinirole). Results indicated that dopamine agonists increased both adaptive and aberrant salience in PD patients, that is, formation of real and illusory associations between conditioned stimuli and reward, respectively. This effect was present when associations were assessed by means of faster responding after conditioned stimuli signaling reward (implicit salience) and overt rating of stimulus-reward links (explicit salience). However, unusual feelings and experiences, which are subclinical manifestations of psychotic-like symptoms, were specifically related to irrelevant and illusory stimulus-reward associations (aberrant salience) in PD patients receiving dopamine agonists. The learning of relevant and real stimulus-reward associations (adaptive salience) was not related to unusual experiences. These results suggest that dopamine agonists may increase psychotic-like experiences in young patients with PD, possibly by facilitating dopaminergic transmission in the ventral striatum, which results in aberrant associations between conditioned stimuli and reward.